1993
DOI: 10.1080/00288233.1993.10417734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbage species on gastro-intestinal roundworm populations and their distribution

Abstract: Sheep faeces containing strongylate eggs were applied to plots of perennial ryegrass, prairie grass, or chicory mixed with white clover, or lucerne without white clover. Plots were later harvested within four height zones and the herbage mass, numbers, and species of gastro-intestinal nematodes determined. Ryegrass, prairie grass, and lucerne plots produced similar yields of herbage dry matter (DM) (3580, 3180, and 3230 kg DM/ha respectively), whereas chicory produced 2250 kg DM/ha. Ryegrass-, prairie grass-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 7 publications
(12 reference statements)
2
31
0
1
Order By: Relevance
“…The purpose of the present experiment was to ascertain the larval population within the expected lamb grazing zone, hence the cutting height and interval selected. Increasing the sward density increased the number of larvae recovered from herbage, and this concurs with the findings of Moss & Vlassoff (1993) when they compared various pasture species that generated differences in sward density. They, and Knapp (1964), concluded that denser swards created more favourable microclimates for the development and survival of trichostrongylid larvae.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The purpose of the present experiment was to ascertain the larval population within the expected lamb grazing zone, hence the cutting height and interval selected. Increasing the sward density increased the number of larvae recovered from herbage, and this concurs with the findings of Moss & Vlassoff (1993) when they compared various pasture species that generated differences in sward density. They, and Knapp (1964), concluded that denser swards created more favourable microclimates for the development and survival of trichostrongylid larvae.…”
Section: Discussionsupporting
confidence: 76%
“…In the present experiment, had herbage been cut to ground level, it is likely more larvae would have been recovered, as according to Vlassoff (1982), more exist nearer ground level. However, this would not necessarily have yielded more per kg of DM as Moss & Vlassoff (1993) found the concentration of larvae was lowest in ryegrass swards within 0-25 mm of ground level compared to higher zones. The purpose of the present experiment was to ascertain the larval population within the expected lamb grazing zone, hence the cutting height and interval selected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moss & Vlassoff (1993) found that ryegrass-and prairie grass-based swards contained more nematode larvae than did lucerne, which in turn contained more than chicory. A similar observation was made by Scales et al (1995) in a lamb grazing experiment which compared a pasture with low endophyte ryegrass, cocksfoot, and tall fescue with a pasture containing lucerne and chicory.…”
Section: Introductionmentioning
confidence: 99%